Hubungan Pola Asuh Orang Tua Dengan Tingkat Perkembangan Bahasa dan Perkembangan Sosial Balita Di Puskesmas BP Nauli Kecamatan Siantar Marihat Kota Pematangsiantar Tahun 2023 - Juliati Lestari Pasaribu; Asnita Sinaga; Isyos Sari Sembiring; Indra Agussamad (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Parenting is a parenting style that provides teachings to toddlers that will aim to shape the child's characteristics, provide education that can shape the toddler's personality and provide support in the development process, both growth and development and related to the toddler's skills. In implementing parenting patterns, parents discover the unique behavior of toddlers because the characteristics of children are very different, so parents need to pay attention to their children and provide different parenting patterns for each toddler. Parenting for toddlers will be carried out under the age of 5-6 years, during this time the attention given to the child must be more active where parents pay attention to their development and growth, mental, physical, social development and the interactions carried out every day (Rahmat, 2018). In line with previous research conducted by Sisri Landa Sari, entitled the relationship between parenting patterns and children's social development in Jorong Kampung VII District. South Rao District. Pasaman in 2019, where research results showed that there was a significant relationship between parental parenting patterns and the social development of children under five with a correlation coefficient of 0.350 and a significant p-value of 0.010<0.05, which means that the higher the parenting pattern, the the higher the level of social development of the child, and vice versa, if the toddler receives low parenting, the social development of the toddler will be low (Sari, 2019).Based on the initial survey conducted at the BP Nauli Community Health Center, Siantar Marihat District, Pematangsiantar City, it can be seen that there are two villages and there are toddlers whose language and social development is still lacking, this is because the parents of these toddlers are not often near their children all the time because the parents are older. there is a lot of time to work and farm to earn a living so that the development experienced by children is given less attention and the parents' knowledge about the development of toddlers is lacking. .Keywords: Parenting Patterns, Toddler Development.